A retrospective study on causes of unsafe abortions in referred patients, at a tertiary care centre in western Uttar Pradesh - Kulshrestha, Kalpna; Gupta, Barkha; Verma, Kalpana; Tarun, Mandvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Unsafe abortions occur when pregnancy is terminated by unqualified person or in an environment that do not conform to minimal medical standards or both. The aim of this study was to analyse the causes in referred patients of unsafe abortions, methods used and complications with which patients were admitted. Methods: A retrospective observational study conducted in the department of Obstetrics and Gynaecology, SIMS Hapur Uttar Pradesh, India from 1stJune 2019 to 29thFebruary 2020. Data was collected from previous hospital records. Total 150 women aged between 18-40 years, admitted with complications of unsafe abortions and who had taken advice for termination outside our institute, were included. The demographic profile, detailed history, first contact person for abortion advice, abortion service provider, method of termination and prior ultrasound were noted. Exclusion criteria was period of gestation more than 20 weeks and spontaneous abortions. Results: The study showed 92% contacted unqualified person, out of which 22.5%were uncertified doctors, 30.4% ANM’s, 16.7% Nurses, 12.3% consulted quacks and 10.9% Chemists. Among the abortion service providers 23.6% were uncertified doctors, 45.7% Chemists, 15% Nurses, 5.7% Quacks, 3.6% ANM’s and 6.4% had taken self-medication. Prior ultrasound was done in 28% cases. Method of termination was medical in 78.7% and surgical in 21.3% cases. Period of gestation was <8 weeks in 69.3%, 8-12 weeks in 27.3%, 12-16 weeks in 2%. 37.3% had parity 2 and 55.3% were Hindus. Conclusions: Despite availability of safe abortion services, unsafe abortion practices are still prevalent. Approved MTP centres, skilled and certified abortion providers must be easily accessible to women even in rural areas to safeguard their health.